Does European-style welfare generosity discourage single mother employmnet? - Lane Destro; David Brady (Luxembourg Income Study (LIS), 2010)
Although many have expressed concern over whether generous welfare policies discourage the employment of single mothers, scholars have rarely exploited cross-national variability in the generosity of social policies to assess this question. This is the case even though much previous scholarship has examined the effects of social policy on women's and mothers' labor force engagement. This paper evaluates whether generous social policies have a disincentive effect on single mother employment. Using the Luxembourg Income Study (LIS), we conduct a cross-national, multi-level analysis of the effects of social policy generosity on single mother employment in 17 affluent democracies. We find high rates of single mother employment - above 60 percent in 15 of the 17 countries and above 70 percent in 5 countries. We find little effect of social policy for employment, as our two measures of social policy are insignificant in almost all models. If there are welfare disincentives, they only appear significant for young single mothers, and this evidence is limited as well. We find contradictory evidence for the employment incentive for low educated single mothers. We determine that single mother employment is largely driven by the same individual characteristics - educational attainment, age and household composition - that drive employment in the general population, and among women and mothers. To the best of our knowledge, this is one of the few cross-national, multi-level tests of the welfare disincentive thesis for single mother employment. We provide evidence that welfare generosity does not discourage single mother employment.
Keywords: 330; research paper; disincentive; single mothers; employment; cross-national; social policy; Erwerbstätigkeit; Alleinerziehende; Mütter; Sozialpolitik; Wirkungsanalyse; OECD-Staaten